The Computer Software Industry in East and West: Do Eastern European Countries Need a Specific Science and Technology Policy? - Jürgen Bitzer (Deutsches Institut für Wirtschaftsforschung (DIW), 1997)
National science and technology (S&T) systems are often mentioned as a condition for competitiveness of high technology sectors. Therefore, public S&T policies should actively support the development of national S&T systems. In particular in Eastern Europe an active S&T policy is often demanded to support the development of the supposed domestic high technology potential. This paper shows that this hypothesis is ill-founded in the case of the software sector. With an industrial economic analysis of the software sector it is shown, that a S&T policy is widely not able to fulfil this expectation. The analysis of the different market segments: standard and individual software, shows that the competition is carried out on axes which can widely not be influenced by a S&T policy. The links between software enterprises and the S&T systems are very weak, which is the result of the conditions of software development and the competition axes used in the software industry. Therefore, only few, and very general, starting points remain for an active S&T policy. Main starting points are: the improvement of the education in modern software technology, improvement of patent protecting laws and their enforcement, and introduction of standardisation procedures and quality standards. – – Nationale Innovationssysteme werden häufig als Voraussetzung für die Wettbewerbsfähigkeit von Hochtechnologiebranchen angesehen. Für Regierungen besitzt eine aktive Innovationspolitik einen hohen Stellenwert. Besonders in Osteuropa wird oft eine aktive Innovationspolitik gefordert, um die Entwicklung des vermuteten Hochtechnologiepotentials zu unterstützen. Dieses Papier zeigt, daß diese Hypothese für die Softwarebranche nicht gehalten werden kann. Mit Hilfe einer industrieökonomischen Analyse der Softwarebranche wird gezeigt, daß eine Innovationspolitik die in sie gesetzten Erwartungen weitestgehend nicht erfüllen kann. Die Analyse der Marktsegmente Standard- und Individualsoftware zeigt, daß der Wettbewerb auf Achsen stattfindet, die von einer Innovationspolitik weitestgehend nicht beeinflußt werden können. Als Ergebnis der Art und Weise wie Software entwickelt wird und der verwendeten Wettbewerbsachsen sind die Verbindungen zwischen den Softwareunternehmen und dem Innovationssystem schwach. Für eine aktive Innovationspolitik verbleiben daher nur wenige Ansatzpunkte. Als Hauptansatzpunkte werden eine Verbesserung der Ausbildung mit moderner Softwaretechnologie, eine Verbesserung des Patentschutzrechtes und seiner Durchsetzung sowie die Einführung von Stadardisierungsprozeduren und Qualitätsstandards identifiziert.
Keywords: P51; L63; L11; 330; Softwareindustrie; Industrieökonomik; Innovationspolitik; Osteuropa; Welt